THE EFFECT OF PRODUCT QUALITY AND BRAND IMAGE ON THE PURCHASE DECISION OF MS.GLOW SKINCARE PRODUCTS THROUGH PURCHASE INTEREST AS A MEDIATION VARIABLE IN USERS OF MS.GLOW SKINCARE PRODUCTS IN TERNATE - Fadila Ahmad; Ida Hidayanti; Johan Fahri (Journal of Management and Islamic Finance, 2022)
This study aims to determine the effect of product quality and brand image on purchasing decisions through buying interest. This research was a quantitative research. The population in this study were consumers using skincare ms.glow products in Ternate with the sampling method, namely Non-Probability Sampling with a purposive sampling approach. The data analysis technique was path modeling analysis using Smart Partial Least Square (PLS) version 3 as a statistical test tool. The results of this study indicate that product quality has a significant effect on purchasing decisions, brand image has no significant effect on purchasing decisions, product quality has a significant effect on buying interest, brand image has a significant effect on buying interest, buying interest has a significant effect on purchasing decisions, product quality has a significant effect on purchasing decisions through buying interest, and brand image has a significant effect on purchasing decisions through buying interest.